2023
DOI: 10.3390/zoonoticdis3040021
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic Diseases in Sub-Saharan Africa: A Systematic Review and Meta-Analysis

Jérôme Ateudjieu,
Joseph Nelson Siewe Fodjo,
Calson Ambomatei
et al.

Abstract: Frequent animal–human interactions in sub-Saharan Africa (SSA) pose an increased risk for the transmission of zoonotic diseases. While there are sporadic reports of zoonotic diseases outbreaks in SSA, a synthetic overview is necessary to better understand how the sub-region is impacted by these pathologies. We conducted a systematic review of zoonotic diseases studies conducted in SSA between 2000 and 2022. Quantitative reports including case reports/series from countries spanning West, Central, East, and Sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…Most rural communities worldwide were reported using herbs concoctions as uterotonics (to speed labour process), to support safe childbirth and improve the welfare of babies however, some herbs reported having side effects like, uterine rupture, placenta abruption, post-partum haemorrhage (PPH), foetal distress and infertilities as major complications [19]. In that case, the integration between health facilities and community systems can play a very big role in improving maternal health eventually reduces maternal death [20,21,22,23]…”
Section: Home Deliverymentioning
confidence: 99%
“…Most rural communities worldwide were reported using herbs concoctions as uterotonics (to speed labour process), to support safe childbirth and improve the welfare of babies however, some herbs reported having side effects like, uterine rupture, placenta abruption, post-partum haemorrhage (PPH), foetal distress and infertilities as major complications [19]. In that case, the integration between health facilities and community systems can play a very big role in improving maternal health eventually reduces maternal death [20,21,22,23]…”
Section: Home Deliverymentioning
confidence: 99%
“…The taro plant is a tuber plant that has long been known and used by Indonesian people [1]. Taro plants in Indonesia consist of several genera, namely the genus Xanthosoma sagittifolium (L.) Schott, the genus Colocasia esculenta (L.) Schott (taro Bogor) and the genus Colocasia gigantea (Blume ex Hassk.)…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence to suggest that intensive meat production and consumption is detrimental to environmental and human health. For instance, research has shown that red meat (mainly processed meat) consumption has the potential for various cardiovascular diseases, some types of cancer and various instances of food borne infections and zoonosis (Ateudjieu et al., 2023; Delia Grace et al., 2012). Moreover, it is expected that by 2030, the livestock sector, the main source of dietary protein, could account for 27%–49% of the greenhouse gasses (GHGs) emissions.…”
Section: Introductionmentioning
confidence: 99%